The Effect Of Organizational Communication On Teacher Performance At Sma Negeri 5 Banjarmasin - Muhammad Agus Humaidi; Mohammad Ali Wafa (Institute of Computer Science (IOCS), 2022)
Teachers are an internal part of an educational organization that has a very strategic function, role and position in order to achieve the nation's development goals in the field of education. Teachers are at the forefront of implementing various educational programs through learning activities. So that the success and quality of educational programs designed by educational policy makers, one of which is very dependent on the performance of teachers. In this regard, modern society as it is today always demands the fulfillment of the needs of good and quality education for its children. Society is increasingly challenging, requiring and demanding the implementation of professionally managed education and supported by high teacher performance. The research which will be carried out within a period of four months is aimed at knowing the description of organizational communication and teacher performance at SMA Negeri 5 Banjarmasin, in addition to knowing the effect of organizational communication on teacher performance at SMA Negeri 5 Banjarmasin. The method used is a quantitative research approach and a research instrument with a questionnaire which is analyzed with Simple Linear Regression. The results showed that organizational communication and teacher performance at SMA Negeri 5 Banjarmasin were in the good category. Organizational communication has a significant effect on teacher performance at SMA Negeri 5 Banjarmasin, as evidenced by the significance value of 0.000 <0.05 and the tcount 10.175> ttable 2.003. The value of the termination coefficient (R2) or the magnitude of the influence of the teacher performance variable caused by organizational communication was found to be 67.2%.